Sebastiana Petrycego z Pilzna pouczenia „jak się zachować czasu moru” – instrukcja, nauka czy poradnik? : Rekonesans badawczy historyka literatury. - Wichowa, Maria (Tematy i Konteksty, 2021)
Analyzed in this study text by Sebastian Petrycy containing tips on how to act during the epidemic plague, is difficult to classify in terms of genre. According to the author, it is an instruction which was to provide the advice and instruction to the users of this work. During the research carried out here, a specific genre syncretism of Petrycy's „Instruction” was demonstrated. This work was examined in terms of literary communication, the interaction assumed by the author between the author of the work and its recipient, and therefore the dialogical nature of the text was analyzed, which is very important in providing its user with instructions, advice and tips. It was show that the „Instruction” has no "purity" of genre, that it evidently has a mixture of the features of "science book" and a guide. In contemporary research, the „Instruction” has been seen as a guide.